MULTI LEVEL MARKETING DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Safwan Safwan (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
Amid the sluggishness and deterioration of the national economy, came a business system that had much promise and success and offered wealth in a short time. This system became known as Multi Level Marketing (MLM) or Networking Marketing. Multi Level Marketing (MLM) systems cut distribution channels in conventional sales because it doesn't involve distributors or sole agents and wholesalers or sub-agents, but directly distributing products to independent distributors who work as retailers or sellers directly to consumers. In this way, marketing and distribution costs (transportation, warehouse rent, salaries and sales force commissions etc.) can be obtained transferred to an independent distributor with a system tiered which is generally adjusted to the achievement of targets the sales or turnover of the distributor concerned, coupled with the controversies regarding the MLM system in today's society, starting from the aspect of products that must be halal to the system transactions, bonus giving, member recruitment, and coaching who do not use things that are forbidden by Islam, then plus the elements of money games, maysir, dharar, dzulm, immoral and usury. So it becomes interesting when we see Multi Level Marketing (MLM) through the perspective of Islamic business ethics.